Compound Heterozygous COX20 Variants Impair the Function of Mitochondrial Complex IV to Cause a Syndrome Involving Ophthalmoplegia and Visual Failure - Li, Peizheng; Guo, Dandan; Zhang, Xiufang; Ji, Kunqian; Lv, Hongbo; Zhang, Yanli; Chen, Zhichao; Ma, Jun; Fang, Yaofeng; Liu, Yiming (Frontiers in Neurology, 2022)
The cytochrome c oxidase 20 (COX20) gene encodes a protein with a crucial role in the assembly of mitochondrial complex IV (CIV). Mutations in this gene can result in ataxia and muscle hypotonia. However, ophthalmoplegia and visual failure associated with COX20 mutation have not been examined previously. Moreover, the mechanism causing the phenotype of patients with COX20 variants to differ from that of patients with mutations in other genes impairing CIV assembly is unclear. In this investigation, the aim was to assess the relation between COX20 variants and CIV assembly. We performed detailed clinical, physical, and biochemical investigations of affected individuals. Western blotting, reverse transcription-polymerase chain reaction, and blue native-polyacrylamide gel electrophoresis were used to analyze the expression level of COX20 and oxidative phosphorylation. A Seahorse XF Cell Mito Stress Test and enzymatic activity analysis were performed to evaluate mitochondrial function. Whole-exome sequencing revealed the same compound heterozygous mutations (c.41A>G and c.222G>T, NM_198076) in COX20 in two siblings. This is the first description of ophthalmoplegia and visual failure associated with COX20 variants. In vitro analysis confirmed that the COX20 protein level was significantly decreased, impairing the assembly and activity of CIV in patients’ fibroblast. Overexpression of COX20 using a transduced adenovirus partially restored the function of the patients’ fibroblasts. Early onset complex movement disorders may be closely related to COX20 variants. Our results broaden the clinical phenotypes of patients with COX20 variants showing ophthalmoplegia and visual failure. Additionally, dysfunction of COX20 protein can impair the assembly and activity of CIV.